Mineralization of 14C-diuron by Acinetobacter baumannii. - ROQUE, M. R. A. (1998)
The diuron [3-(3,4-dichlorophenyl)-1,1-dimethylurea] is an herbicide used in sugarcane and other crops. This work evaluated the mineralization of the herbicide diuron by Acinetobacter baumannii and also was developed protocols for extraction and quantification of 14C-diuron. The strain (D12-12), isolated from rhizosphere of sugarcane, grown in soils treated with the herbicide, was cultivated in mineral media J.E. plus diuron at 20 ug/ml and plus 14C-diuron (specific activity = 2.43 MBq/mg) applied at 39,3215 KBq/50 ml, and incubated for 32 days in duplicate. The 14C-diuron extraction was carried out on C-18 SEP-PAK columns, resuspended in scintillation cocktail and the activity determined by liquid scintillation counting. The recuperation of diuron was more than 96,2% and 14CO2 accumulated after 32 days was 1,77%.